2017
DOI: 10.5606/tftrd.2018.1016
|View full text |Cite
|
Sign up to set email alerts
|

Low back pain in hemodialysis patients: Risk factors and its impact on health-related quality of life

Abstract: Objectives:The aim of this study was to evaluate frequency and characteristics of low back pain and to identify possible risk factors of low back pain and its impact on health-related quality of life in hemodialysis patients. Patients and methods:A total of 87 hemodialysis patients (41 males, 46 females; mean age: 53.3±15.8 years; range, 21 to 80 years) were included in the study between January 2015 and July 2015. Medical charts and face-to-face interviews were used to collect clinical and demographic data. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 23 publications
(25 reference statements)
1
9
2
Order By: Relevance
“…Labor-related variables were employment status (“employer”, “self-employed”, “regular employee”, and “non-regular employee”) [ 22 ], income level (low: <4 million JPY; intermediate: 4–7 million JPY; high: >7 million JPY; and unknown or no answer) [ 20 ], and working time (<35, 35–39, 40–44, or >45 h/week) [ 23 ]. We adjusted for health-related status as follows: smoking status (never, former, and current), alcohol use (never, former, and current), and comorbidities (hypertension, diabetes, asthma, chronic obstructive pulmonary disease, cardiovascular disease, stroke, cancer, and psychiatric disorders) [ 24 , 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Labor-related variables were employment status (“employer”, “self-employed”, “regular employee”, and “non-regular employee”) [ 22 ], income level (low: <4 million JPY; intermediate: 4–7 million JPY; high: >7 million JPY; and unknown or no answer) [ 20 ], and working time (<35, 35–39, 40–44, or >45 h/week) [ 23 ]. We adjusted for health-related status as follows: smoking status (never, former, and current), alcohol use (never, former, and current), and comorbidities (hypertension, diabetes, asthma, chronic obstructive pulmonary disease, cardiovascular disease, stroke, cancer, and psychiatric disorders) [ 24 , 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
“… 6 , 7 The QOL of these patients is associated with socio-demographic factors such as age, sex, level of education, and marital status, 8–10 clinical characteristics such as primary disease, comorbidities, and duration of hemodialysis, 11 , 12 as well as chronic pain factors including the duration of pain, pain severity, pain affect, the location of pain. 5 , 13 , 14 Most importantly, psychosocial factors such as social support, self-efficacy, and depression, can also significantly affect QOL. 15–17 …”
Section: Introductionmentioning
confidence: 99%
“…6,7 The QOL of these patients is associated with socio-demographic factors such as age, sex, level of education, and marital status, [8][9][10] clinical characteristics such as primary disease, comorbidities, and duration of hemodialysis, 11,12 as well as chronic pain factors including the duration of pain, pain severity, pain affect, the location of pain. 5,13,14 Most importantly, psychosocial factors such as social support, self-efficacy, and depression, can also significantly affect QOL. [15][16][17] Social support is defined as the interpersonal transaction involving one or more of the following: (1) emotional concern (liking, love, empathy), (2) instrumental aid (goods or services), ( 3) information (about the environment), or (4) appraisal (information relevant to self-evaluation).…”
Section: Introductionmentioning
confidence: 99%
“…Another study of Bilge K was reported 36.7% patients had bodyache. 29 The reason might be due to poor health associated quality of life in patients taking hemodialysis treatment.…”
Section: Resultsmentioning
confidence: 99%